Role Of Agnikarma In Pain Management- A Review - Gurjar, Rohitash; Sharma, Sanjeev; Kumar, Hemantha; Singh, Narinder (International Research Journal of Ayurveda & Yoga, 2021)
Acharya Sushruta who is worshipped as the Father of surgery has described various modalities relating to both surgical and para surgical procedures. Agnikarma (Thermal Cautery), an ancient para surgical modality, Acharya Sushruta elaborated the concept of considering the feasibility and effectiveness of the use of Agni karma in numerous diseases. Which are still applicable in the present era. Agni karma (Thermal Cautery) has given a special place in surgery by Sushruta and it is believed that diseases treated by Agni karma (Thermal Cautery) never reoccur. Pain has been given utmost importance even in Ayurveda, Despite recent advances in pain management including anesthesia, its’ management remains challenging. This article deals with the facts about pain, its management through the conceptual study of vitiation of Vata Dosha responsible for pain, with therapeutic procedure Agni krama utilized in Ayurveda with modern outlook. The proposed hypothesis of increase and decrease the bio signaling pathway leading to Dhatukshaya (depletion of body tissues) and Margavrodhjanya Vata Prakopa (obstructive vata prakopa) could pave the way in understanding the vitiation of Vata Dosha leading to inflammatory pathology. This article attempts to touch maximum aspect of pain management through Agni karma (Thermal Cautery).